2021
DOI: 10.1038/s41598-021-83948-w
|View full text |Cite
|
Sign up to set email alerts
|

Multiple analyses of various factors affecting the plantlet regeneration of Picea mongolica (H. Q. Wu) W.D. Xu from somatic embryos

Abstract: Picea mongolica, a native species with excellent industrial wood quality and strong sand-fixing capacity, may be utilized in construction of urban green spaces in arid areas in China. However, now the sustainability of the ecosystems where this species grows is at serious risk due to a lack of natural regeneration. In this study, we developed an efficient regeneration system and comprehensively analyzed various factors affecting somatic embryogenesis (SE) using zygotic embryos as explants. We identified the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Previous studies have reported that a higher accumulation of starch in cucumber EC may be a necessary prerequisite for further embryonic cell division [25]. In a study of Picea balfouriana and P. mongolica, it was also found that starch and sucrose metabolism are important pathways affecting SE ability [14,26]. In Pinus koraiensis, it has been shown that the production and quality of SE are regulated by glutathione metabolism, and exogenous glutathione was also found to promote SE by increasing intracellular SOD activity, reducing cell death, and promoting intracellular ROS metabolism [27].…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have reported that a higher accumulation of starch in cucumber EC may be a necessary prerequisite for further embryonic cell division [25]. In a study of Picea balfouriana and P. mongolica, it was also found that starch and sucrose metabolism are important pathways affecting SE ability [14,26]. In Pinus koraiensis, it has been shown that the production and quality of SE are regulated by glutathione metabolism, and exogenous glutathione was also found to promote SE by increasing intracellular SOD activity, reducing cell death, and promoting intracellular ROS metabolism [27].…”
Section: Discussionmentioning
confidence: 94%
“…The most pressing challenge is to understand the molecular regulation of embryogenesis in conifers, the knowledge of which remains very limited [123], largely due to the lack of identified embryonic defective mutants [124]. In conclusion, it would be desirable to further develop clear, detailed, and reliable protocols, which are essential for the mechanization and homogenization of experimental systems and, to this end, all mechanisms and resources for vegetative propagation and plant regeneration should be investigated [125].…”
Section: Breeding Programs and Biotechnological Alternativesmentioning
confidence: 99%
“…Transcriptome sequencing can comprehensively and quickly obtain transcripts of specific organs or tissues at a certain state, and it is an important technical way to reveal the gene expression profiling of cells and tissues [37][38][39][40]. Research showed that auxin was crucial for early embryo patterning and pre-cotyledon embryonic formation, while ABA was a major regulator of embryonic maturation by transcriptome, the key genes related to embryo development were obtained and used to improve the efficiency of the somatic embryo (SE) in Picea mongolica [41,42]. Transcription factors, hormone signals, and transduction-related and sugar-metabolism-related genes play a crucial role in barley grain development [3,43].…”
Section: Introductionmentioning
confidence: 99%